Analisis Faktor Risiko Terjadinya Stres Oksidatif Pada Wanita Obesitas - Alpha Olivia Hidayati; Ernawati Hardani (LPPM STIKES Guna Bangsa, 2019)
Obesity is a condition of imbalance in the number of calories entered by the number of calories where the excess is heaped up as body fat. Obesity followed by an increase in fat metabolism will cause Reactive Oxygen Species (ROS) production to increase. This condition causes oxidative stress. Indicators of oxidative stress can be observed from plasma levels of Malondialdehyde (MDA). This study aims to determine the risk factors for oxidative stress in obese women. The results of this study indicate that high fat intake (> 60 g / day) is at risk of increasing MDA-P levels twice. Low fiber consumption (<30 gr / day) gives the risk of an increase in MDA-P levels of 2.09 times. Poor physical activity is a risk factor for MDA-P increase of 1.15 times. High cholesterol (> 200mg / l) and LDL (> 130 mg / l) and low HDL (≤45mg / dl) levels are at risk of increasing MDA-P levels by 1.02 times (cholesterol), 1.13 (LDL) ) and 1.12 (HDL). Based on this study it can be concluded that high fat intake, low fiber intake, low physical activity, high cholesterol and HDL levels and low HDL levels are risk factors for oxidative stress.